Contribution and interaction of the low‐density lipoprotein cholesterol to high‐density lipoprotein cholesterol ratio and triglyceride to diabetes in hypertensive patients: A cross‐sectional study. Issue 1 (24th May 2018) - Hong, Mengyang; Ling, Yan; Lu, Zhiqiang; Liu, Ying; Gu, Ping; Shao, Jiaqing; Gao, Xin; Li, Xiaomu
Abstract: Aims/Introduction: Hypertension is one of the most significant risk factors for diabetes. The present study aimed to investigate the associations of lipid profiles, including the ratio of low‐density lipoprotein cholesterol (LDL‐C)‐to‐high‐density lipoprotein cholesterol (HDL‐C) and triglyceride (TG) levels, as well as their interactions, with type 2 diabetes in hypertensive patients. Materials and Methods: Hypertensive patients without a history of diabetes and hypolipidemic agents were enrolled continuously at the Hypertension Clinic, Zhongshan Hospital, Fudan University (Shanghai, China) from 2014 to 2016. General clinical data, including body mass index, blood pressure, fasting glucose and 2‐h post‐load glucose levels, and lipid profiles, were collected. The LDL‐C/HDL‐C ratio, TG/HDL‐C ratio and TC/HDL‐C ratio were separately calculated. Statistical analyses were carried out by using SPSS software (version 13.0). Results: In total, 935 hypertensive patients were included, of which 114 patients (12.2%) were diagnosed with diabetes. After multivariate adjustments, the LDL‐C/HDL‐C ratio and TG levels had the most significant and independent associations with diabetes. In the multivariate logistic regression, the LDL‐C/HDL‐C ratio and TG were independently associated with diabetes. After the interaction variable was included, the LDL‐C/HDL‐C ratio remained independently associated with diabetes, but TG was replaced by TG*LDL‐C/HDL‐C. Conclusions: In conclusion, elevated LDL‐C/HDL‐C ratios and TG levels were associated with diabetes in patients with hypertension, with an interactive effect of the LDL‐C/HDL‐C ratio and TG on diabetes in the hypertensive population. Abstract : This study demonstrated that lipid profiles, including increased TG levels and LDL/HDL ratios, were independently associated with diabetes in Chinese hypertensive patients. Moreover, TG levels and the LDL/HDL ratio had an interactive effect on diabetes in hypertensive individuals. Our findings provided new insights on controlling multiple lipid profiles in the prevention and treatment of diabetes in hypertensive patients.